The effect of a proposed device on learning the skill of handstand on the parallel device for men - AHMED OKAB AL-HUSEEINAWI, NADIHM (International Journal of Psychosocial Rehabilitation, 2020)
In order for workers to achieve the goals, the steps of the work must be distinguished in succession; that is, the process of development takes a continuous form. The need for the innovation process is achieved in all fields and shows the extent of the discrepancy between the previous work steps if they are compared to the new steps and built according to the foundations identified by the need highlighted by the application process field.